ANALISIS KINERJA BERBASIS KEPUASAN KERJA KARYAWAN - Safari, Teti (UPAJIWA : Jurnal Ekonomi, Bisnis dan Manajemen Daulat Rakyat, 2018)
The purpose of this study was to test the Style of Leadership, Motivation and Discipline Work on the Performance and job satisfaction as an intervening variable BMT Niten Case Study In Bantul. Research conducted in the Credit Unions and Islamic Financing (KSPPS) Baitul Maal Wa Tamwil (BMT) Niten of Bantul. Respondents who used as many as 35 employees working in the Office of BMT. Data were processed using analysis Partial Least Squares (PLS), the SEM-based variance, with SmartPLS 3.0 software. The results showed leadership style had no significant effect on job satisfaction. Motivation does not have a significant effect on job satisfaction. Work discipline has a significant effect on job satisfaction. While the Style of Leadership, Motivation and Work Discipline simultaneously have a significant influence on job satisfaction.   Keywords: Leadership Style, Motivation, Discipline Work, Job Satisfaction on Employee Performance.